HLA-related genetic susceptibility in autoimmune hepatitis according to autoantibody profile - Cancado, Eduardo Luiz Rachid; Goldbaum-Crescente, Juliana; Terrabuio, Debora Raquel B. (Frontiers in Immunology, 2022)
Although the prevalence of autoimmune hepatitis in first-degree relatives is small, the relationship between genetic markers, especially human leucocyte antigens (HLA), and susceptibility to this disease, has been studied for over three decades. The genetic susceptibility to AIH is believed to be different in the two subtypes of the disease, AIH type 1 and AIH type 2. Type 1 AIH has anti-smooth muscle and anti-nuclear antibodies as its main markers, while those of type 2 AIH are the anti-liver/kidney microsome type 1 and anti-liver cytosol type 1 antibodies. The anti-soluble liver antigen/liver-pancreas antibodies, which, in addition to being present in both subtypes, mark an important number of patients without serological markers. Therefore, a third type of disease is questioned. The vast majority of immunogenetic studies compare the differences between the two main types and make no difference between which antibodies are present to define the subtype. This review seeks to analyze what was most important published in the AIH in this context, trying to relate the HLA alleles according to the AIH marker autoantibodies.